ANALISIS UPRATING PENGHANTAR JTM UNTUK PERBAIKAN NILAI DROP VOLTAGE DAN LOSSES PADA PENYULANG KAONAK PT PLN (PERSERO) ULP WAMENA KOTA - Karomi, M. Aslam; Adhi Nugroho, Agus (Elektrika, 2026)
This study aims to evaluate the impact of uprating the Kaonak feeder conductor on energy distribution efficiency and voltage quality. The methods used include literature review, documentation, and interviews to collect relevant data. The literature review covers theories of electric power distribution systems, documentation includes electrical data from PT PLN (Persero) UP3 Wamena, and interviews are conducted with related parties to obtain in-depth information regarding the planned configuration of the Kaonak feeder. Data from the calculation of energy distribution efficiency percentage and voltage drop percentage obtained from ETAP simulations are analyzed quantitatively and compared with the medium-voltage network criteria based on SPLN No. 72 of 1987.The results show that the energy distribution efficiency under existing conditions is 97.34% and the voltage quality is 97.75%, while after reconfiguration these values increase to 97.81% and 96.30%, respectively. This study implies that reconfiguration can improve energy distribution efficiency and voltage quality. Further research is needed to monitor the long-term implementation of the reconfiguration.
Keywords: Efficiency, Energy, Voltage, ETAP